Peningkatan Hasil Belajar Matematika Siswa Kelas VI SDN 013 Sukamaju Menggunakan Model Numbered Heads Together pada Materi Bilangan Bulat - Suratmi, Suratmi (Indo Green Journal, 2024)
The low learning outcomes in mathematics in whole numbers in class VI at SDN 013 Sukamaju can be seen from the 32 students, 18 students scored below the KKM or incomplete category, and 14 students scored above the KKM or completed category. Apart from that, student activity is still relatively low. The aim of this research is that using the Numbered Heads Together Structure model can improve student learning outcomes in mathematics subjects, the main material of integers for class VI SDN 013 Sukamaju, 2022/2023. This research uses 2 cycles of classroom action research, each cycle consisting of planning, implementation, observation and reflection. The target of this research was class VI students at SDN 013 Sukamaju. The data collection techniques used in this research are observations filled in by supervisors and student evaluations given at the end of the learning process. Based on the results of the analysis, it was found that in cycle 1 learning activities the students who achieved the KKM score were 14 students or 44% of the 32 students. In learning cycle 2, 27 students scored KKM or 85% of the 32 students. From these data it can be concluded that the Numbered Heads Together Structure learning model can improve student learning outcomes in mathematics subjects covering integers in class VI SDN 013 Sukamaju in the 2022/2023 academic year.